Negative Cultures for Cerebrospinal Fluid Samples taken from the Myelomeningocele Sac on the Day of Repair - Mayol, Miguel; Pamias, Eva F.; Pellot, Joel; Vigo, Juan (Puerto Rico Health Sciences Journal, 2020)
Objective: Our goal was to evaluate the intraoperative laboratory analysis of cerebrospinal fluid (CSF) aspirated from the myelomeningocele (MMC) sac prior to the repair to determine if there was bacterial growth in the culture. Methods: This was a retrospective analysis of the CSF cultures of 45 MMC patients operated on during the years of 2002 to 2013 at the University Pediatric Hospital. Before repairing the defect, the sac area was cleaned and three milliliters of CSF were drawn and sent for analysis for red blood cells, white blood cells, glucose level, protein level, chloride level, gram stain and culture. The CSF sample results were analyzed for irregularities in the values before proceeding with placement of a ventricular shunt. Results: All the CSF samples that were studied had at least 1 abnormal value in their results, even though none grew any pathogens in the cultures analyzed. Conclusion: Upon CSF analysis, we found increased levels of CSF protein and other abnormal values in this population; however, none of the cultures grew any pathogens. This finding is an important tool in the evaluation of the possible etiologies of and therapeutic approaches for future shunt problems in this group of patients.